Prevalence and Factors Associated With Virological Treatment Failure Among Children and Adolescents on Antiretroviral Therapy Attending HIV/AIDS Care and Treatment Clinics in Dodoma Municipality, Central Tanzania. (28th May 2020) - Bitwale, Niyonziza Z; Mnzava, David P; Kimaro, Francisca D; Jacob, Theopista; Mpondo, Bonaventura C T; Jumanne, Shakilu
Abstract: Background: As the World Health Organization (WHO) and its joint partners such as USAIDS target achieving 90% sustained virological suppression among children and adolescents living with Human Immunodeficience Virus (HIV)/AIDS, it is imperative to elucidate the current prevalence and factors associated with virological treatment failure for formulation of appropriate strategies. This study was conducted determine the prevalence and factors associated with virological treatment failure among children and adolescents with HIV/AIDS on antiretroviral therapy (ART) attending HIV/AIDS care clinics in Dodoma, Central Tanzania. Methods: This was a cross-sectional study of children aged 1–19 years attending 3 HIV/AIDS care clinics in Dodoma (central Tanzania) from November 2018 to February 2019. Sociodemographic and clinical factors were documented, HIV viral load and CD4+ T lymphocytes were evaluated for children on ART for ≥6 months. The primary outcomes were the prevalence and factors associated with viralogic treatment failure. Results: Of 300 children enrolled, 102 (34%) had virological treatment failure. Poor adherence to ART (adjusted odds ratio [AOR] = 3.221; 95% confidence interval [CI], 1.867–5.558; P = .032), nevirapine regimen (AOR = 3.185; 95% CI, 1.473–6.886; P ≤ .001), not using cotrimoxazole prophylaxis (AOR = 25.56; 95% CI, 3.15–27.55; P = .002) and nondisclosure of HIV status to others (AOR = 7.741; 95% CI, 2.351–25.489; P = .001) were independently associated with virological treatment failure. Conclusions: Current prevalence of virological treatment failure among children and adolescents living with HIV on ART remain high. Factors such as ART adherence, nevirapine based regimen, HIV status disclosure to those caring for the child need to be addressed to achieve sustained virological suppression.